Evolutionary patterns and research frontiers in autophagy in podocytopathies: a bibliometric analysis - Liu, Feng; Xu, Ziyu; Chen, Gaijie; Xu, Xiaojing; Cao, Huixia; Chen, Jiefang (Frontiers in Medicine, 2025)
IntroductionPodocytopathies are a uniquely renal disease syndrome, in which direct or indirect podocyte injury leads to proteinuria or nephrotic syndrome. Of the many factors that contribute to podocytopathies, the abnormal regulation of autophagy, such insufficient or excessive autophagy levels, have been proposed to play a significant role in the occurrence and development of podocytopathies. However, there still has been a lack of systematic and comparative research to elucidate exact role of autophagy in podocytopathies and its current research status. This study aims to utilize bibliometric analysis to clarify the role of autophagy in the pathogenesis of podocytopathies, analyze the research focus in this area, as well as explore the future research trends.MethodsWe retrieved original articles and review papers with respect to autophagy in podocytopathies research published between the year 2008 and 2022 from the Web of Science Core Collection (WOSCC). Then, VOSviewer and CiteSpace software were employed to reveal the leading subjects and generate visual maps of countries/regions, organizations, authors, journals, and keyword networks in this field.Results and discussionA total of 825 publications regarding autophagy in podocytopathies published between 2008 and 2022 were included, with China contributing the most followed by the United States and Japan. Professor Koya Daisuke, Professor He Qiang, and Professor Jin Juan are the most prolific researchers in this field. Oxidative stress, the NLRP3 inflammasome, and therapeutic targets were the knowledge base for the research in this special field. Taken together, this bibliometric analysis helps us reveal the current research hotspots and guide future research directions, which provides a reference for scholars to further investigate the role of autophagy in podocytopathies as well as conduct clinical trial with autophagy regulators in podocytopathies.